Dynamic characteristics of a new remote transformer current converter with compensating capacitor - Babanazarova N.K. (Genius Journals, 2023)
In the paper analytical equations of transient characteristics of a new remote transformer current converter with a compensating capacitor are obtained when a jumping, linearly increasing, sinusoidal and sinusoidal with damped amplitude influences are applied to their input. It is shown that the developed current converter can be represented in structural schemes of control and management systems in the form of a series-connected ideal differentiating link, a real differentiating link without statism and an inertial link of the second order, and in the case of neglecting active losses in the magnetic core - in the form of a series-connected ideal differentiating and oscillating links. It is established, for the case of connection of the primary circuit of the current converter to the network of sinusoidal current with damped amplitude, that at δ>ω_0 (where δ is the damping coefficient and ω_0 is the natural angular frequency of the secondary circuit) the transient current of the secondary circuit consists of the sum of two free aperiodic and forced damped sinusoidal components, at δ=ω_0 - one free aperiodic and forced damped sinusoidal components, and at δ <ω_0 - one free and one forced damped sinusoidal components, the degree of damping of which depend on the time constants of the secondary and primary circuit of the current converter, respectively. >
Keywords: Remote current converter; multifilament core; effect